ISO 9001:2015 BASED EDUCATION QUALITY ASSURANCE SYSTEM MODEL IN IMPROVING EDUCATION QUALITY - Musalam; Agus Zaenul Fitri; As'aril Muhajir (International Journal of Multidisciplinary Reseach, 2026)
Educational development in the global era demands educational institutions to improve service quality systematically and sustainably. However, a gap remains between the quality of educational services and stakeholders' needs. This study aims to analyze the implementation of the ISO 9001:2015-based quality management system in enhancing educational quality, as well as to formulate its implementation components and stages within the context of educational institutions. The research problem focuses on how the concepts, principles, and implementation models of ISO 9001:2015 can be integrated into the education quality assurance system. This study employs a qualitative approach using the library research method, with data gathered from scientific journals, academic books, ISO documents, and educational regulations. Data analysis was conducted using the content analysis technique to review and synthesize relevant concepts. The results show that the implementation of ISO 9001:2015 can enhance educational quality through process-based and risk-based approaches, supported by the principles of customer focus, leadership, and human resource engagement. Furthermore, integrating components such as organizational context, the PDCA cycle, and risk management, alongside systematic implementation stages, can strengthen the internal quality assurance system (SPMI) and boost the competitiveness of educational institutions